2015
DOI: 10.1590/1414-431x20154732
|View full text |Cite
|
Sign up to set email alerts
|

Cotransfected human chondrocytes: over-expression of IGF-I and SOX9 enhances the synthesis of cartilage matrix components collagen-II and glycosaminoglycans

Abstract: Damage to cartilage causes a loss of type II collagen (Col-II) and glycosaminoglycans (GAG). To restore the original cartilage architecture, cell factors that stimulate Col-II and GAG production are needed. Insulin-like growth factor I (IGF-I) and transcription factor SOX9 are essential for the synthesis of cartilage matrix, chondrocyte proliferation, and phenotype maintenance. We evaluated the combined effect of IGF-I and SOX9 transgene expression on Col-II and GAG production by cultured human articular chond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Meanwhile, we verified that upregulation of miR-195 suppressed FGF-18 expression and the activity level of its downstream FGFR3/ FGFR3 p-Tyr724 , ERK1/2/ERK1/2 p-Thr202/Tyr204 , and SOX9. SOX9, which was well accepted as the upstream regulator of Col2a1 and aggrecan [62,63,64,65,66], was reported as being regulated by FGF-18 according to former studies [67,68]. Furthermore, in the present study, we also showed that ectopic miR-195 could correspondingly regulate the expression of FGF-18 and its downstream SOX9 and further effect the expression of Col2a1 and aggrecan.…”
Section: Discussionsupporting
confidence: 78%
“…Meanwhile, we verified that upregulation of miR-195 suppressed FGF-18 expression and the activity level of its downstream FGFR3/ FGFR3 p-Tyr724 , ERK1/2/ERK1/2 p-Thr202/Tyr204 , and SOX9. SOX9, which was well accepted as the upstream regulator of Col2a1 and aggrecan [62,63,64,65,66], was reported as being regulated by FGF-18 according to former studies [67,68]. Furthermore, in the present study, we also showed that ectopic miR-195 could correspondingly regulate the expression of FGF-18 and its downstream SOX9 and further effect the expression of Col2a1 and aggrecan.…”
Section: Discussionsupporting
confidence: 78%
“…Naturally, mutations affecting the function of these transcription factors would affect the integrity of the ECM by altering its composition. Most of the transcription factors included on the list fall in this category, often regulating directly the expression of collagen, fibronectin, or cadherin genes (Bi et al, ; Hsieh et al, ; Cho et al, ; Papangeli and Scambler, ; Simental‐Mendia et al, ; Horie et al, ; Yoh et al, ). Transcriptional control might be contextual as seen with the Saethre–Chotzen gene TWIST1 (101400) that can both upregulate and downregulate collagen expression (Fang et al, ; Garcia‐Palmero et al, ).…”
Section: Ecm Expression During Palatal Growthmentioning
confidence: 99%
“…In their study, the resulting heterogeneity in the expression of transfected genes was analyzed on the single-cell level for the fast and efficient characterization and optimization of synthetic genetic systems and circuits [ 38 40 ]. Functional relevance of the integrated co-transfection method has been addressed in a study by Mendia et al, suggesting the highest cartilage matrix deposition secreted by integrated co-transfected human chondrocytes expressing both IGF-I and SOX9 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%